Improving cardiovascular outcomes among Aboriginal Australians: Lessons from research for primary care. (25th November 2016) - Thompson, Sandra C; Haynes, Emma; Woods, John A; Bessarab, Dawn C; Dimer, Lynette A; Wood, Marianne M; Sanfilippo, Frank M; Hamilton, Sandra J; Katzenellenbogen, Judith M
Background: The Aboriginal people of Australia have much poorer health and social indicators and a substantial life expectancy gap compared to other Australians, with premature cardiovascular disease a major contributor to poorer health. This article draws on research undertaken to examine cardiovascular disparities and focuses on ways in which primary care practitioners can contribute to reducing cardiovascular disparities and improving Aboriginal health. Methods: The overall research utilised mixed methods and included data analysis, interviews and group processes which included Aboriginal people, service providers and policymakers. Workshop discussions to identify barriers and what works were recorded by notes and on whiteboards, then distilled and circulated to participants and other stakeholders to refine and validate information. Additional engagement occurred through circulation of draft material and further discussions. This report distils the lessons for primary care practitioners to improve outcomes through management that is attentive to the needs of Aboriginal people. Results: Aspects of primordial, primary and secondary prevention are identified, with practical strategies for intervention summarised. The premature onset and high incidence of Aboriginal cardiovascular disease make prevention imperative and require that primary care practitioners understand and work to address the social underpinnings of poor health. Doctors are well placed to reinforce the importance of healthy lifestyle at all visits to involve the family and to reduce barriers which impede early care seeking. Ensuring better information for Aboriginal patients and better integrated care for patients who frequently have complex needs and multi-morbidities will also improve care outcomes. Conclusion: Primary care practitioners have an important role in improving Aboriginal cardiovascular care outcomes. It is essential that they recognise the special needs of their Aboriginal patients and work at multiple levels both outside and inside the clinic for prevention and management of disease. A toolkit of proactive and holistic opportunities for interventions is proposed.